Augustine and the environment - Doody, John, 1943- (Augustine in conversation., 2016)
This volume examines Augustine's writings and shows their importance for framing questions of human and divine nature, as both shape our concept of and relationship to the environment. These essays will further any discussion on Christianity and the environment.